New Insights into Aminoglycoside Antibiotics and Derivatives - Silva, Julierme G.; Carvalho, Ivone (Current Medicinal Chemistry, 2007)
In the post-genome era, RNA has emerged as a valid molecular target involved in many biochemical pathways such as cellular protein interactions. This includes transcription and translation, HIV-Rev and HIV-tat proteins binding to HIV RNA that encode HIV genetic information. The binding of natural and synthetic aminoglycosides to RNA or RNA-protein complexes has been a central focus of small molecules-RNA recognition events, since they bind selectively to a variety of RNA targets. The understanding of the contribution of shape-based and charge motifs involved in aminoglycosides-RNA complexes gives remarkable information of the translational miscoding process, thereby opening new insights for drug discovery. This review comprises relevant information about aminoglycosides antibiotics, including chemical structure, molecular mechanism, structureactivity relationships, recent advances in aminoglycoside mimetics over the last four years, resistance mechanisms and structuretoxicity relationships.
Keywords: aminoglycoside mimetics